EDITORIAL COMMENT ON THE ARTICLE OF O.V. RESHETKO ET AL. "ANALYSIS OF PRE-HOSPITAL TREATMENT OF ACUTE CORONARY SYNDROME" (Столичная издательская компания, 2015)
Editorial comment on the article of O.V. Reshetko et al. "Analysis of pre-hospital treatment of acute coronary syndrome".